Anaerobic Bio-Methane Potential of the Liquors from Hydrothermal Carbonization of Different Lignocellulose Biomasses - Diaz-Robles, L; Huilinir-Curio, C; Montalvo-Martinez, S; Pages-Diaz, J (Elsevier Ltd, 2020)
In this work, the spent liquor of pine sawdust (L1), canola oil waste (L2), olive oil waste (L3) and vineyards waste (L4) from hydrothermal carbonization (220 °C, 1 h) process were studied as substrates for biogas production. Kinetic degradation using three kinetic models (Gompertz model, Hill model and Chapman model) was also analyzed. The batch experiments showed that the highest methane yield (253 NmLCH4/gCODadded) and higher soluble Chemical Oxygen Demand (sCOD) removal efficiency (71%) was achieved for the spent liquor of L1, reaching up to 81% of the theoretical methane yield. The liquid fractions of L2, L3 and L4 resulted in lower yields (24 ̶ 36% of the theoretical yield) and lower sCOD removal (40 ̶ 45%), which can be related to the presence of recalcitrant nitrogen materials formed during the HTC. Gompertz model better represents the performance of the liquor fractions (L1 and L2), having long lag phase (5–7 days), while Chapman model adjusted the accuracy of the behavior of L3 and L4 (lag phase < 1 days). As a conclusion, the spent liquor coming from HTC process of lignocellulosic biomass waste can be used as resource to recover energy through anaerobic digestion. © 2020 Elsevier Ltd